1997
DOI: 10.1016/s0005-2736(97)00025-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the interaction of hydrophobically-modified poly-(N-isopropylacrylamides) with liposomes

Abstract: Interactions of hydrophobically-modified poly-(N-isopropylacrylamides) (HM PNIPAM) with phospholipid liposomes were studied as a function of the lipid type, the lipid bilayer fluidity, and the polymer conformation. Fluorescence experiments monitoring non-radiative energy transfer (NRET), between naphthalene attached to the HM PNIPAM and 1,6-diphenyl-1,3,5-hexatriene (DPH) incorporated into the lipid bilayer, confirmed the direct penetration of hydrophobic anchor groups linked to the polymer into the liposome h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 20 publications
0
61
0
Order By: Relevance
“…Accordingly, the DPPC bilayers are always in the gel state for all the rheology measurements in our study, whereas the EPC bilayers having a phase transition temperature from À15 to À5°C are in the fluid state. A previous study on HMPNIPAM with DMPC (T m % 23.5°C) and EPC [31] found that the bilayer fluidity appeared not to affect the polymer binding efficiency, while a more uniform distribution of hydrophobes was detected for liposomes in the fluid state. The hydrophobes were thought to exchange faster and more dynamically between water and bilayers in the fluid state than in the gel state.…”
Section: Viscosity Behavior Of Hmhec-phospholipid Vesicles Solutionmentioning
confidence: 81%
See 2 more Smart Citations
“…Accordingly, the DPPC bilayers are always in the gel state for all the rheology measurements in our study, whereas the EPC bilayers having a phase transition temperature from À15 to À5°C are in the fluid state. A previous study on HMPNIPAM with DMPC (T m % 23.5°C) and EPC [31] found that the bilayer fluidity appeared not to affect the polymer binding efficiency, while a more uniform distribution of hydrophobes was detected for liposomes in the fluid state. The hydrophobes were thought to exchange faster and more dynamically between water and bilayers in the fluid state than in the gel state.…”
Section: Viscosity Behavior Of Hmhec-phospholipid Vesicles Solutionmentioning
confidence: 81%
“…Unlike surfactant vesicles, no phase separation was observed for phospholipid vesicles mixed with HMPs [25][26][27][28][29][30][31][32]. Phospholipid vesicles naturally mimic the biological cells, making them a better candidate in the study of fundamental interaction between cells and polymers [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Other researchers have reported that even a small number of long alkyl side chains can facilitate the deeper insertion of poly(N-isopropylacrylamides) derivatives into the liposomal bilayer. 32 The ability of PLP-NDA 18% to hemolyze RBCs at endosomal pH 5.5 and physiological pH was further evaluated as a function of polymer concentration ( Figure 3B). PLP-NDA 18%…”
Section: Cell Membrane Disruptionmentioning
confidence: 99%
“…Like conventional detergents, macromolecules can however strongly modulate the permeability of the membrane (9)(10)(11)(12), modify the curvature energy (13), and solubilize lipids in mixed micelles (14). The enhancement of liposome fusions can also result from polymer adsorption as reported by Polozova and Winnick in the case of modified poly(N -isopropylacrylamide) (15), by Kono et al on the example of decyl-modified poly(glycidol)s (16), or by Hara et al on an amphiphilic polymer consisting of octadecylacrylamide and N,N-dimethylacrylamide (17). At variance with conventional detergent molecules, the structure of a polymer can be varied in a continuous manner, by changing gradually the charge density or the hydrophobicity of long chains, making it possible to tune the stability of vesicles.…”
Section: Introductionmentioning
confidence: 99%